Bacteriophages as an Up-and-Coming Alternative to the Use of Sulfur Dioxide in Winemaking - Cordero-Bueso, Gustavo; Moraga, Javier; Ríos-Carrasco, María; Ruiz-Muñoz, Marina; Cantoral, Jesús Manuel (Frontiers in Microbiology, 2020)
Certain acetic and lactic acid bacteria are the major causes of quality defects in musts and wines, giving rise to defects such as "vinegary", "sharp like nail polish remover" or preventing alcoholic and/or malolactic fermentation. Sulfur dioxide is the major tool currently used in the control of these bacteria in wine. The aim of this work was to isolate bacteriophages from musts and wine of different grape varieties, able to eliminate lactic and acetic acid bacteria spoilages at laboratory scale. Musts obtained from grape-berries of Vitis vinifera cv. Chardonnay and Moscatel and a red wine made with Vitis vinifera cv. Tintilla de Rota were used to isolate bacteriophages. Bacteriophages were obtained from all musts and wine, belonging to the order Caudovirals and to the family Tectivirals. They were isolated by classical virology methods and identified by electron microscopy. Host-bacteria used in the study were the lactic acid bacteria of the species Lactobacillus hilgardii, L. plantarum and Oenococcus oeni and the acetic bacteria Acetobacter aceti. A comparative study was performed on musts and wines, previously inoculated with bacteria, by phage titration and SO2 addition to study the effectiveness of bacteriophages against bacteria. The comparative study showed that some bacteriophages were as effective as sulfur dioxide at low concentration.